2017
DOI: 10.19082/5402
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in Iran: A meta-analysis

Abstract: BackgroundMetabolic syndrome) MetS( is a complex risk factor which increases the risk of cardiovascular diseases and type 2 diabetes. There are many studies with various populations and results about the prevalence of MetS in Iran; in order to authenticate these studies and have an overall estimation of its prevalence in Iran, performing a meta-analysis seems to be necessary.ObjectiveThis study aimed to investigate the prevalence of MetS and its components in Iran via meta-analysis method.MethodsAll associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 71 publications
4
15
1
Order By: Relevance
“…Metabolic syndrome (MetS) is a progressive problem worldwide that is associated with increased risk of chronic diseases (Ranasinghe et al, 2017;Pasdar et al, 2019a). MetS is highly prevalent in industrial and developing countries, although the highest prevalence occurs in developing countries (Ostovar et al, 2017;Hajian-Tilaki, 2018). Recent results from a systematic review have shown that the prevalence of MetS in adults (≥18 years of age) is 31.6% in Iran (Ostovar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic syndrome (MetS) is a progressive problem worldwide that is associated with increased risk of chronic diseases (Ranasinghe et al, 2017;Pasdar et al, 2019a). MetS is highly prevalent in industrial and developing countries, although the highest prevalence occurs in developing countries (Ostovar et al, 2017;Hajian-Tilaki, 2018). Recent results from a systematic review have shown that the prevalence of MetS in adults (≥18 years of age) is 31.6% in Iran (Ostovar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MetS is highly prevalent in industrial and developing countries, although the highest prevalence occurs in developing countries (Ostovar et al, 2017;Hajian-Tilaki, 2018). Recent results from a systematic review have shown that the prevalence of MetS in adults (≥18 years of age) is 31.6% in Iran (Ostovar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to urbanization, excessive energy intake, increased obesity, and sedentary lifestyle; metabolic syndrome has become one of the leading public health concerns worldwide (1). Central obesity, dyslipidemia, increase in high-density lipoprotein cholesterol levels, high serum triglyceride, insulin resistance, and type 2 diabetes are also some of the risk factors for metabolic syndrome (2). The patients with metabolic syndrome have a higher risk for various types of diseases and there are also some degrees of disability and mortality in these patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a comprehensive study in Iran over 12 years (from 2001 to 2013) indicated a 6.9% increase in the spread of metabolic syndrome [4][5][6][7][8][9]. Increase in the prevalence of MetS is possibly as a result of genetic factors, unhealthy lifestyle and environmental conditions [4][5][6][7][8][9]. These observed spread rates are higher than the predicted spread around the world, which is between 20% and 25% [10].…”
Section: Introductionmentioning
confidence: 99%